Factors affecting career progression of female academics to senior positions: A case study of Open University of Tanzania - Tarimo, Elias Adolf (Mzumbe University, 2024)
A dissertation submitted to the School of Public Administration and Management in partial fulfillment of the requirements for the award of the degree of Master of Science in Human Resource Management of Mzumbe University